Contemporary Mechanical Circulatory Support With Continuous-Flow Biventricular Assist Devices: A Systematic Review. Issue 4 (11th October 2021) - Meece, Lauren E.; Yu, Julia; Jeng, Eric I.; Ahmed, Mustafa M.
Abstract : As the incidence of heart failure increases, so too has that of biventricular failure. While transplantation remains the gold standard therapy for end-stage heart failure, the limited organ supply has increased the need for durable mechanical circulatory support. We therefore sought to conduct a systematic review of continuous-flow ventricular assist devices in a biventricular configuration (CF-BiVAD). An electronic search of PubMed and Cumulative Index to Nursing and Allied Health Literature (CINAHL) databases was performed using the keyword "BIVAD." Studies were reviewed to identify discrete variables, including implant indication, INTERMACs profile, timing of implant, mean age and BMI, and the anticoagulation/antiplatelet regimens employed post implant. Outcomes of interest included mortality and the incidence of thrombus, bleeding, infection, stroke, and renal failure. A total of 25 studies met inclusion criteria. No single variable was consistently reported, with only 4 studies reporting all 5 adverse effects. INTERMACs profile at implant and anticoagulation/antiplatelet regimen were reported in less than 50% of studies. Of those reporting mortality, there was a wide range of follow-up, from less than 6 months to >10 years, and the survival rate was similarly widely variable. Additionally, more than 50% of studies failed to isolate CF-BiVAD from alternative means of biventricular support, such as temporary support platforms, TAH, and pulsatile VADs. Therefore, high-quality quantitative analysis is not possible. In summary, the CF-BiVAD literature has a very heterogenous reporting of data. Standard reporting criteria may allow for future analyses to determine which patient characteristics portend a favorable outcome with CF-BiVAD implantation.